Enantioselective Palladium-Catalyzed Suzuki–Miyaura Reactions Enabled by Ionic Ligand–Substrate Interactions - On, Ivan K. W.; Zhu, Ye (Synlett, 2023)
Enzymes harness an array of noncovalent interactions to accomplish stereospecific transformations. Similarly, chemists have engineered chiral catalysts capable of eliciting noncovalent interactions for asymmetric synthesis. In this context, incorporating ionic groups into synthetic transition-metal catalysts represents a promising design element for enantioselective reactions by engaging electrostatic interactions between ligands and substrates. However, the nondirectional nature of ionic interactions presents a unique challenge in precise transmission of chirality. This account summarizes our recent work on developing phosphine ligands possessing nonligating ionic groups for exerting long-range stereocontrol in Suzuki–Miyaura reactions.1 Introduction2 Remote Quaternary Stereocenters3 Mechanically Planar Chiral Rotaxanes4 Atropo-enantioenriched Biaryls5 Conclusions
Keywords: stereoselectivity; cross-coupling; noncovalent interactions; quaternary stereocenters; rotaxanes; atropisomerism; mechanically planar chirality; ionic interactions